Increased diazinon hydrolysis to 2-isopropyl-6-methyl-4-pyrimidinol in liquid medium by a specific Streptomyces mixed culture. (August 2016) - Briceño, G.; Schalchli, H.; Rubilar, O.; Tortella, G.R.; Mutis, A.; Benimeli, C.S.; Palma, G.; Diez, M.C.
Abstract: Actinobacteria identified as Streptomyces spp. were evaluated for their ability to remove diazinon as the only carbon source from a liquid medium. Single cultures of Streptomyces strains were exposed to diazinon at a concentration of 50 mg L −1 . After 96 h incubation, six of the eight cultures grew and five strains showed an increase in their total protein concentrations and changes in their protein profile. Up to 32% of the diazinon was removed by the single Streptomyces cultures. A compatibility assay showed that the different Streptomyces species were not antagonistic. Twenty-six mixed cultures were then prepared. Diazinon removal was increased when mixed cultures were used, and maximum diazinon removal of 62% was observed when the Streptomyces spp. strains AC5, AC9, GA11 and ISP13 were mixed; this was defined as the selected mixed culture (SMC). Diazinon removal was positively influenced by the addition of glucose into the liquid medium. Our study showed a diazinon degradation rate of 0.025 h −1, half-life of 28 h −1 and 2-isopropyl-6-methyl-4-pyrimidinol (IMHP) production of 0.143 mg L h −1 . Rapid diazinon hydrolysis to IMHP was associated with a decrease in the pH of the medium as a consequence of microbial glucose metabolism and organic acid exudation. Moreover, the SMC of Streptomyces was able to remove IMHP. This work constitutes a new, if not the only, report on diazinon degradation by mixed cultures of Streptomyces spp. Given the high levels of diazinon removal, the SMC formed by four Streptomyces strains has the potential to be used to treat the diazinon present in environmental matrices. Graphical abstract: Highlights: Diazinon is used as an only carbon source for growth by studied Streptomyces . Mixed cultures of Streptomyces spp. increase the diazinon removal. Formation of the diazinon metabolite 2-isopropyl-6-methyl-4-pyrimidinol was observed. Glucose metabolism stimulate changes in the culture increasing diazinon hydrolysis. Selected mixed culture of Streptomyces spp. remove diazinon and its metabolite.